Optimum Conditions for Pyomelanin Production and Characterization from Local Isolates of Pseudomonas aeruginosa - Naz Fuad H. Khorshid; Nisreen Hadi Odaa (Medical Journal of Babylon)
Background: Nowadays, there is increased interest in the biosynthesis of microbial melanin related to their numerous biological functions and applications in many fields, especially in medical fields, including immune-modulating, antimicrobial antibiotic, antiviral antivenin, anticancer, antitumor activity, and anti-biofilm activity. Pyomelanin is a hydrophobic macromolecule that is typically dark brown or black in color, formed by the oxidative polymerization of phenolic or indolic compounds. Pyomelanin is reported to be safe for consumption, thus providing a crucial strategy for biocontrol of biofilm. Furthermore, natural pyomelanin is known as a potent antioxidant, photoprotective, and free radical scavenging. Objective: This study focuses on the extraction and parametric optimization of melanin using Pseudomonas aeruginosa (P. aeruginosa) isolates. Materials and Methods: P. aeruginosa was isolated from various clinical sources, including urinary tract infections, burn patients, and wound infections. The isolate’s identification was done by biochemical, cultural, and VITEK-2 compact system. The isolates were subjected to pyomelanin production in nutrient agar supplemented with L-tyrosine, and the potential isolate was selected and employed for melanin production using nutrient broth supplemented with L-tyrosine. The pyomelanin-producing isolates were further identified through the PCR analysis technique. Different physical parameters were used for optimum pyomelanin yield. Results: The potential P. aeruginosa isolates were further identified using 16s rRNA. Pyomelanin production was better at 2.9 µg/mL at 100 rpm. The highest pyomelanin production was 3.07 µg/mL after 72 h incubation. The optimum pH at 7 was 3.12 µg/mL. The highest pyomelanin yield at 40°C was 3.03 µg/mL, while the maximum pyomelanin was produced using 2 g/L tyrosine at 2.99 µg/mL. UV-visible (UV-Vis) spectroscopy analysis for pyomelanin pigment was at 273.5 nm. The infrared spectrum exhibited a broad absorption band around 3280.82 cm−1 which corresponds to the presence of -OH and N-H groups. Conclusion: This study provides knowledge on factors affecting pyomelanin production using bacteria in broth media supplemented with L-tyrosine.